Change in Food and Beverage Availability and Marketing Following the Introduction of a Healthy Food Financing Initiative–Supported Supermarket. Issue 4 (May 2019) - Singleton, Chelsea R.; Li, Yu; Odoms-Young, Angela; Zenk, Shannon N.; Powell, Lisa M.
Purpose: The Healthy Food Financing Initiative (HFFI) aims to expand access to healthy foods in low-resourced communities across the United States. This study examined changes in food and beverage availability and marketing in nearby small food stores after the opening of an HFFI-supported supermarket in a predominately low-income and African American community. Design: Natural experiment. Setting: Rockford, Illinois. Participants: A full audit was conducted of the small grocery and limited service stores located in a 1-mile radius around the new supermarket (N = 22) and a 1-square mile area within a nearby demographically matched comparison community (N = 18). Stores were audited in 2015 (1 month preopening) and 2016 (1 year afterward). Measures: Store characteristics, item availability, and interior and exterior promotions/advertisements were examined. Analysis: Difference-in-difference (DID) regression models assessed pre- and postintervention changes in availability and marketing between small food stores in the intervention and comparison communities. Results: The DID regression models indicated no difference between intervention and comparison communities with respect to changes in availability and marketing of all food items with the exception of frozen vegetables which had higher availability postintervention in the comparison community versus intervention (β for interaction term = .67; standard error: 0.33; P = .04). Conclusion: After the opening of the HFFI-supported supermarket, food and beverage availability and marketing in nearby small food stores did not change significantly. However, the wide range of staple foods offered by the supermarket contributed to the expansion of healthy food retail in the intervention community.